PENGEMBANGAN APLIKASI BERBASIS DIGITAL SANTABASUN UNTUK MENGENALKAN KESANTUNAN BERBAHASA SUNDA PADA SISWA SEKOLAH DASAR - Nurfarida, Sallsa; Iswara, Prana Dwija; Gusrayani, Diah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This application aims to introduce Sundanese politeness to elementary school students, especially fourth graders. The resulting product is a digital application called SANTABASUN, which was developed using Smart Apps Creator, Canva, and Capcut software. The data collection process was carried out through interviews, questionnaires filled out by validators, material experts, media experts, and user responses filled out by students. This study used the ADDIE development model which consists of five stages, nameIy anaIysis, design, deveIopment, impIementation, and evaluation. The results showed that the SANTABASUN application has met the eligibility criteria. Based on the assessment by media experts, the application obtained a score of 96% which is categorized as very feasible, while the materiIl experts obtained a score of 87% which is also categorized as very feasible. In terms of user response, the smaIIl group trial produced a percentage of 94% and is categorized as very good, while the large group trial obtained a percentage of 97% which is also categorized as very good. These findings indicate that the SANTABASUN application is considered effective and suitabIe for use as an interactive Iearning medium to introduce Sundanese politeness. The application's strengths lie in its attractive appearance, relevant content, and visual and audio support, which aid comprehension. However, there's still ample potential for further development, such as expanding the user base to various groups and educational levels, and adding a variety of materials to enhance comprehensive learning.